Evaluation of functional and bioactive properties of crude gill extract of Tor putitora using different assays. (17th August 2022) - Rehman, Gauhar; Sardar, Sumbal; Alkhateeb, Mariam Abdulaziz; Mohamed, Rania Ali El Hadi; Abd Al Galil, Fahd Mohammed; Hamayun, Muhammad; Shahjeer, Kiran; Iqbal, Toheed; Ahmed, Nazeer; Nawaz, Taufiq; Ullah, Rafi
Summary: For centuries, natural products isolated from animals, plants and microbes have been the centre of attention for the world's scientific community for their role in eradicating and reducing many diseases. The present research work is also performed on the crude gill extract of Tor putitora named TPG‐Ex to analyse its various functional and bioactive properties. A total of five different biological assays were performed. Two assays performed were the free radical scavenging assays having other free radical generators such as DPPH and H2 O2 . Different concentrations of extract were used in both assays. The maximum scavenging ability in the Antioxidant DPPH assay was 59.42% at 50 μL. In the H2O2 radical scavenging assay, the maximum scavenging ability of TPG‐Ex recorded was 55.46% at a concentration of 50 μL. The antiangiogenic potential of the TPG‐Ex CAM assay was assessed, which also showed maximum inhibition of neovascularisation at a concentration of 80 μL. The antidiabetic potential of TPG‐Ex was also revealed after processing the extract through glucose uptake by yeast cells assay and glucose adsorption assay. TPG‐Ex indicated maximum glucose uptake at a concentration of 20 μg of 56.61%.